Malaysian Carbon Reduction and Environmental Sustainability Tool (MyCREST) Qualified Professional Training Assessment - Mustaffa Kamal, Mohd Firdaus; Mohd Affandi, Haryanti; Sohimi, Nurul Eizzaty; Abdul Musid, Nor Hafizah; Mohd Ali, Mohd Rizalman; Mat Nashir, Irdayanti (Journal of Technical Education and Training, 2019)
In assessing the green building application, CIDB has introduced the Malaysian Carbon Reduction and Environmental Sustainability Tool (MyCREST) which will be fully implemented for government project starting in the year 2018. In order to spread the awareness of MyCREST implementation and train the MyCREST assessor, and TVET workforce, CIDB has conducted series of MyCREST training every year. This research aims to investigate the overall performance of MyCREST training through the training objective assessment method. This research was carried out during the MyCREST in-house training by CIDB involving 33 trainees from all over Malaysia. A questionnaire survey has been developed for this research, and the data has been analyzed using descriptive statistical analysis. Result from this research determined that the majority of the respondents who completed this training have acquired new knowledge on MyCREST. It can be concluded that MyCREST training has achieved the objectives set out by the CIDB. However, in order to improve and to richen the data, observation during the training is suggested to be added in future research.